Азербайджанские ковры - Тагиева, Ройя (Народна творчість та етнологія, 2014)
Ковер – это неотъемлемая часть культуры Азербайджана. Он стал не только предметом быта, но и превратился в основную сферу художественного выражения народа. Даже с изменением в образе жизни, формированием совершенно иной бытовой и художественной среды ковер не терял своего значения. Он всегда оставался основным элементом жизненного уклада, отражая в себе социальные, экономические, политические и культурные изменения в жизни людей и общества в целом. Ковер присутствует в фольклоре, классической азербайджанской литературе и в песнях народных певцов. Carpet is an integral part of the culture of Azerbaijan. It was not only the subject of life, but also became the main sphere of artistic expression of the people. Even with a lifestyle change, the formation of an entirely different household and artistic environment, the carpet had not lost its value. He always remained the focus of lifestyle, reflecting social, economic, political, and cultural changes in the lives of individuals and society as a whole. The carpet is well-presented in folklore, literature, and classical Azerbaijan in songs by folk singers.